Evaluation of key aroma compounds in hand-squeezed grapefruit juice (Citrus paradisi Macfayden) by quantitation and flavor reconstitution experiments - Büttner, Andrea; Schieberle, Peter (Journal of Agricultural and Food Chemistry, 2001)
Twenty-five odor-active compounds were quantified in the fresh, hand-squeezed juice of White Marsh seedless grapefruits using stable isotope dilution assays. By calculation of the odor activity values of the odorants (ratio of their concentrations in the juice to their odor thresholds, in water) it was shown that the fruity esters ethyl 2-methylpropanoate, ethyl butanoate, and (S)-ethyl 2-methyl- butanoate, and the fruity, sweet winelactone, as well as the grassy smelling (Z)-hex-3-enal, and trans-4,5-epoxy-(E)-dec-2-enal with metallic odor, were among the most potent odorants of the fresh grapefruit juice. The typical sulfurous, grapefruit-like odor quality was mainly due to the catty, blackcurrant-like 4-mercapto-4-methylpentan-2-one and the grapefruit-like smelling 1-p-menthene-8-thiol. These findings were confirmed by reconstitution experiments to simulate the aroma of the fresh grapefruit juice.
Keywords: 4-mercapta-4-methylpentan-2-one; 1-p-menthene-8-thiol; hept-1-en-3-one; winelactone; (Z)-hex-3-enal; stable isotope dilution analysis